Peace and disarmament. Soviet proposals. Report by D.T. Shepilov [Šepilov]. Speeches by V.V. Kuznetsov [Kuznecov] at U.N.O. 1957. Disarmament proposals of november 17, 1956 and other documents (London, 1957)
Soviet New Booklet, 1957, 4.